Answer: C
Step-by-step explanation: Consider a triangle with points A, B and C. You must create a perpendicular bisector of AB and then a perpendicular bisector of BC that crosses each other. Then you must label the center of that point D, and then using a compass tool, create a circle around the triangle.
f(x)= -2x-3
Step-by-step explanation:
Step 1:
Let the sequence given here is -5, -7, -9, -11, -13 ......
Here the first term (a₁) of sequence is -5
And the common difference between the numbers in the sequence is
d= (-7-(-5)) = -7+5 = -2
Let the number of terms be x
Step 2;
To find the sequence function basic arithmetic sequence formula is
aₙ = a₁ + d( x-1)
Applying the values we get
f(X) = -5 + ((-2)(X-1))
on simplification
f(X) = -5 + (-2X+2)
f(X)= -5+2-2X
f(X)= -3-2X
15 13/24 or in decimal form 15.5416
Answer: First Option : Sₙ= n/2(a₁ + aₙ)
Step-by-step explanation:
The nth partial sum of an arithmetic sequence or the sum of the first n terms of the arithmetic series can be defined as the sum of a finite number of term in an arithmetic sequence.
It is calculated using the formula:
Sₙ= n/2(a₁ + aₙ)
Where :
a₁ = First term
aₙ = last term
n = number of terms